Meta-Analysis of First-Line Triple Therapy for Helicobacter pylori Eradication in Korea: Is It Time to Change? - Gong, Eun Jeong; Yun, Sung-Cheol; Jung, Hwoon-Yong; Lim, Hyun; Choi, Kwi-Sook; Ahn, Ji Yong; Lee, Jeong Hoon; Kim, Do Hoon; Choi, Kee Don; Song, Ho June; Lee, Gin Hyug; Kim, Jin-Ho (Journal of Korean medical science, 2014)
Proton pump inhibitor (PPI)-based triple therapy consisting of PPI, amoxicillin, and clarithromycin, is the recommended first-line treatment for Helicobacter pylori infection. However, the eradication rate of triple therapy has declined over the past few decades. We analyzed the eradication rate and adverse events of triple therapy to evaluate current practices in Korea. A comprehensive literature search was performed up to August 2013 of 104 relevant studies comprising 42,124 patients. The overall eradication rate was 74.6% (95% confidence interval [CI], 72.1%-77.2%) by intention-to-treat analysis and 82.0% (95% CI, 80.8%-83.2%) by per-protocol analysis. The eradication rate decreased significantly from 1998 to 2013 (P < 0.001 for both intention-to-treat and per-protocol analyses). Adverse events were reported in 41 studies with 8,018 subjects with an overall incidence rate of 20.4% (95% CI, 19.6%-21.3%). The available data suggest that the effectiveness of standard triple therapy for H. pylori eradication has decreased to an unacceptable level. A novel therapeutic strategy is warranted to improve the effectiveness of first-line treatment for H. pylori infection in Korea.